(untitled) (Baghdad Science Journal, 2025)
A new series of transition metal complexes of Cu(II), Ni(II), Co(II) and Fe(III) have been synthesized from the Schiff base (L1) and (L2) derived from Semicarbazide hydro chloride and 4-chlorobenzaldehyde or 4-bromobenzaldehyde. The structural features have been arrived from their elemental analyses, magnetic susceptibility, molar conductivity, IR, UV-Vis. and 1H NMR spectral studies. The data show that the complexes have composition of [M(L)2](NO3)2 and [Fe(L)2 (NO3)2](NO3) where the M=Co(II),Ni(II) and Cu(II) ;L=L1and L2 type. The magnetic susceptibility and UV-Vis spectral data of the complexes suggest a square planer geometry for Co(II) and Cu(II) but Fe(III) octahedral geometry and Ni(II) tetrahedral geometry around the central metal ion.Hyper Chem-6 program has been used to predict structure geometries of compounds in gas phase .The electrostatic potential of the free ligands were calculated to investigate the reactive sites of the molecules .The heat of formation(?Hf ?) and binding energy(?Eb) at 298K for the free ligands and its metal complexes were calculated by using PM3 method.